Molybdenum Stress Modulates Enzymes Responsive to Oxidative Stress and Affects Seeds Viability and Vigor in Chickpea. Issue 1 (2nd January 2017) - Gopal, Rajeev; Shukla, Arvind K.
ABSTRACT: The importance of molybdenum (Mo) for plant growth is disproportionate with respect to the absolute amounts required by most plants. Chickpea ( Cicer arietinum L .) cv. K-75 plants were raised in refined sand in glasshouse at graded levels from 0.002 to 1 µM for 100 days. Mo deficiency symptoms appeared as interveinal chlorosis of middle and old leaves. Compared with the control (0.2 µM Mo), dry matter, yield and seed protein decreased at low and excess Mo. The concentration of Mo in leaves and seed as well as the activity of nitrate reductase (NR) increased with an increase in Mo supply. The activities of antioxidative enzymes stimulate at both low and excess Mo supply. Low and excess Mo decreased the lipid peroxidation status in chickpea leaves, suggesting its antiperoxidative nature. The values of deficiency, threshold of deficiency and threshold of toxicity of Mo were, respectively, 0.38, 1.2 and 15 µg g −1 in leaves of chickpea.